2016
DOI: 10.1038/mt.2015.191
|View full text |Cite
|
Sign up to set email alerts
|

Host Anti-antibody Responses Following Adeno-associated Virus–mediated Delivery of Antibodies Against HIV and SIV in Rhesus Monkeys

Abstract: Long-term delivery of antibodies against the human immunodeficiency virus (HIV) using adeno-associated virus (AAV) vectors is a promising approach for the prevention or treatment of HIV infection. However, host antibody responses to the delivered antibody are a serious concern that could significantly limit the applicability of this approach. Here, we describe the dynamics and characteristics of the anti-antibody responses in monkeys that received either rhesus anti-simian immunodeficiency virus (SIV) antibodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 41 publications
(69 reference statements)
1
87
3
Order By: Relevance
“…17, 18, 33 Comparable to our previous studies using AAV 17, 33 the anti-4L6 responses in our present study with recombinant RRV were higher than the measured responses against 5L7. Furthermore, both recombinant RRV-4L6 recipients showed clear anti-antibody responses, whereas only one of the two recombinant RRV-5L7 recipients exhibited measurable anti-antibodies; this also reflects the AAV results where anti-anti responses were consistently observed in six of six monkeys with 4L6 delivery but only in three of six monkeys with 5L7 delivery.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…17, 18, 33 Comparable to our previous studies using AAV 17, 33 the anti-4L6 responses in our present study with recombinant RRV were higher than the measured responses against 5L7. Furthermore, both recombinant RRV-4L6 recipients showed clear anti-antibody responses, whereas only one of the two recombinant RRV-5L7 recipients exhibited measurable anti-antibodies; this also reflects the AAV results where anti-anti responses were consistently observed in six of six monkeys with 4L6 delivery but only in three of six monkeys with 5L7 delivery.…”
Section: Discussionsupporting
confidence: 61%
“…36, 37 The data of Martinez-Navio et al indicates that the magnitude of the anti-anti response is directly proportional to the distance from the germline of the antibody being delivered. 33 …”
Section: Discussionmentioning
confidence: 99%
“…5B). We observed that the G382R/H442Y variant remained as resistant to the SIV neutralizing antibodies 4L6 and 5L7 (16,17) as wild-type SIVmac239 Env up to concentrations of 50 g/ml, whereas pseudovirus expressing the SIVmac316 Env was efficiently neutralized at the lowest concentration assayed (0.0032 g/ml). Similarly, both the SIVmac239 Env and the G382R/ H442Y variant remained more than 400ϫ more resistant to sera from two infected macaques than SIVmac316.…”
Section: Resultsmentioning
confidence: 86%
“…Expi293 cells were grown in Expi293 expression medium (Thermo Fisher Scientific). Plasmids V132 and V82 for the expression of antibodies 4L6 and 5L7, respectively, were provided by Ronald Desrosiers, as were plasmids encoding SIV mac 239 SpX, SIV mac 316 open SpX, and SIVsmE543-3 full-length viral genomes, and SIVmac251 stock virus (5,16,17,38). SIVmac1A11 infectious molecular clone, also from the NIH AIDS reagent program, was supplied by Paul Luciw (39).…”
Section: Methodsmentioning
confidence: 99%
“…Primate protection from SIV challenge has recently been reported with AAV vector expressing the simianized form of the VRC07 bNAb [49]. Recent work has tackled secondary challenges, such as testing harder-to-neutralize SIV strains and strategies to avoid anti-antibody responses, a major obstacle in developing effective vectored antibody therapies [50]. Fuchs et al recently showed that use of a fully simianized, authentic IgG structure does not ameliorate the immunogenicity of a foreign antibody as hoped [51].…”
Section: Vectored Delivery Of Antibodies and Antibody-like Moleculesmentioning
confidence: 99%